Effect supplementation of baker’s yeast (Saccharomyces cerevisae) on the growth performance and nutrient digestibility in the Japanese quails - Ismail, Siti Noridayu (2016)
The study was conducted to determine the effect of feeding baker’s yeast (Saccharomyces cerevisae) in diets of the growing of Japanese quails. Performance, nutrient digestibility, body weight gain, feed intake, and feed conversion ratio were studied. A total of 112 chicks (one day old unsexed) with the body weights ranging between 8 and 10g were used. The chicks were obtained from a local commercial breeder farm. The chicks were randomly divided into 4 treatments groups consisting of 4 replicates of 7 chicks and fed a starter ration for 2 weeks. After two weeks, they were fed the treatment diets comprising of a commercial grower supplement with yeast. The dietary treatments were control (0%) yeast, treatment 1 (0.5% yeast), treatment 2 (1.0 % of yeast) and treatment 3 (1.5% of yeast). The feeding trial lasted until 42 days of age after which they were slaughtered and dressing percentage determined. The result revealed that, birds fed with diets containing yeast at level 1.5% recorded significantly higher (P< 0.05) body weight gain compared to control diet. The feed conversion ratio significantly higher in dietary treatment with supplemented Saccharomyces cerevisae. After that, feed intake also show that (P>0.05) there were no significant different among the treatment group. The result of dressing percentage showed that the dressing percentage and proportion weight of organ showed no significant difference (P>0.05) among the treatment groups. It can be was concluded that adding yeast 0.05 to 1.5% in the diet improved growth of broiler quails.